Consumer Attitudes Toward Sustainable Strategies in Fashionable Clothing in India - Jain, Prachi (Global journal of Business and Integral Security, 2024)
Amid increasing environmental concerns, the fashion industry’s ecological footprint is under examination. This research centres on India’s Generation Y (born 1982-1994) to understand their inclinations towards sustainable fashion. The study aims to dissect their core values, the external factors influencing their purchasing decisions, their view on industry standards, and their openness to higher prices for sustainable items. By using qualitative tools like surveys and interviews, initial findings stress the significance of cultural, socio-economic, and informational elements. These insights can steer the fashion industry’s sustainable evolution and augment scholarly discussions on sustainable consumerism in emerging markets.